TRATAMENTO DA HIPERTENSAO ARTERIAL LEVE E MODERADA COM FOSINOPRIL. COMPARACAO DE EFEITOS ADVERSOS COM OUTROS ANTI-HIPERTENSIVOS - Martin, Luis Cuadrado [UNESP]; Velasco-Cornejo, I. V. [UNESP]; Da Silva Franco, R. J. [UNESP] (My University, 1994)
Purpose - To evaluate the adverse reactions of fosinopril with other antihypertensives used as monotherapy. Methods - Out-patients (n = 2,568) with diagnostic of mild to moderate hypertension, diastolic blood pressure (DBP) 95-115 mmHg, with no antihypertensive treatment for 15 days, were included to treatment initially with fosinopril (F) 10mg, once daily, for six weeks. After this period, patients with DBP >95mmHg had the dosage, once daily, increased to 20 mg, while the others were maintained with the same dosage for six more weeks. Adverse reactions of 822 patients treated as monotherapy were grouped as absent, musculoskeletal, cardiovascular, cough, gastrointestinal, neurological, genital-urinary dysfunctions and dermatological and compared with 1,568 with F. Monotherapy consist in α-methyldopa (100 patients); β-blocker (129); calcium blocker (106); diuretic (394); and another ACE inhibitors (93). Results - At the end of the period without treatment, the blood pressure (BP), 165 ± 16/105 ± 7 mmHg decreased significantly at 6(th) week to 144 ± 15/91 ± 9 mmHg (p < 0.05 vs week 0) with further lowering to 139 ± 13/86 ± 7 mmHg till the end of 12(th) week. BP response (DBP ≤90 mmHg) was obtained in 89% of the patients with F. Absence of adverse reactions were ≥70% in patients with F compared to other drugs. Conclusion - Fosinopril has demonstrated therapeutic efficacy and less adverse reactions compared to antihypertensives used previously as monotherapy.
Treatment of mild-to-moderate hypertension with fosinopril. Adverse reactions compared with other antihypertensives
Keywords: angiotensin converting enzyme inhibitor; fosinopril; hypertension; beta adrenergic receptor blocking agent; calcium antagonist; dipeptidyl carboxypeptidase inhibitor; diuretic agent; methyldopa; antihypertensive agent; adult; aged; blood pressure; cardiotoxicity; clinical trial; controlled clinical trial; controlled study; coughing; drug efficacy; female; gastrointestinal symptom; human; major clinical study; male; musculoskeletal injury; neurotoxicity; oral drug administration; skin toxicity; adolescent; ambulatory care; comparative study; multicenter study; Adolescent; Adult; Aged; Aged, 80 and over; Ambulatory Care; Antihypertensive Agents; Comparative Study; English Abstract; Female; Fosinopril; Human; Hypertension; Male; Middle Age